New record and potential spatial distribution of Curcuma sumatrana (Zingiberaceae): An endemic wild turmeric in Sumatra, Indonesia - FARADILA SYAFIRA; NURAINAS NURAINAS; SYAMSUARDI SYAMSUARDI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Syafira F, Nurainas, Syamsuardi. 2024. New record and potential spatial distribution of Curcuma sumatrana (Zingiberaceae): An endemic wild turmeric in Sumatra, Indonesia. Biodiversitas 25: 4127-4138. Curcuma sumatrana Miq. is a Sumatran turmeric species with medicinal potential. However, it remains underutilized and is classified as vulnerable by the IUCN. Its vulnerability is aggravated by limited knowledge of its distribution, a need for more data on habitat preferences, and habitat degradation. Field observations revealed significant morphological variations among populations, likely influenced by environmental factors. This study assessed the morphology, microhabitat preferences, and spatial distribution of C. sumatrana in West Sumatra, Indonesia. Surveys and laboratory observations highlighted morphological traits, such as leaf and ligule length and width, significantly contribute to these observed variations. Notably, the leaf shape differed between open and shaded areas, being narrowly elliptic in open areas and broadly elliptic in shaded areas. Populations in Koto Malintang and Lubuk Minturun showed distinct differences, separated by six morphological traits. The C. sumatrana prefers habitats with fertile soils, moderate plant diversity, and open land cover, often coexisting with species like Dendrocnide stimulans (L.fil.) Chew, Macaranga tanarius (L.) Müll.Arg., and Diplazium sp. Maximum Entropy modeling (AUC 0.944) predicted a highly suitable habitat of 918 hectares in the western Bukit Barisan range. The model suggests distribution is influenced by soil type and precipitation patterns during the seasonal, warmest, and coldest quarters, as well as land cover. New records from West Sumatra extend the species' known range, reaffirming its vulnerable status with a potential risk of becoming endangered.